Cerebral blood flow changes during tilt table testing in healthy volunteers, as assessed by Doppler imaging of the carotid and vertebral arteries - van Campen, C. (Linda).M.C. (Clin Neurophysiol Pract, 2018)
OBJECTIVES: Using different techniques, reduction of cerebral blood flow (CBF) during orthostatic stress were demonstrated. One study reported flow reduction of the right internal carotid (ICA) and vertebral (VA) artery during orthostatic stress by Doppler imaging, with different effects on the 2 vessels. Global CBF changes, using this technique, have not been reported. Therefore, flow of the ICA, VA and global CBF were measured during head-up tilt testing. METHODS: 33 healthy volunteers underwent tilt testing. At three time points (supine, half way and at the end of the test) Doppler imaging of the ICA and VA was performed, as well as PetCO2 measurements. RESULTS: Global CBF was significantly reduced by 4.5 ± 2.8% halfway the test and by 6.0 ± 3.4% at the end. All 4 artery flows were significantly reduced during the tilt, without differences between them. Despite small changes in PetCO2 there was a significant relation between de CBF decrease and PetCO2 decrease (p < 0.05). CONCLUSIONS: Orthostatic stress in HV results in a small but significant reduction of CBF by a homogenous reduction in the four cerebral vessels and is modulated by PetCO2 changes. SIGNIFICANCE: CBF changes can be measured during tilt testing using Doppler VA and ICA imaging.